(untitled) - Stuart, Timothy S. (San Francisco, CA, 2005)
This workbook explains the AT PROMISE paradigm and offers stories, activities, self-assessments, prayer reflections, and answers to frequently asked questions, encouraging readers to understand and apply At Promise principles in their daily relationships with kids. Most notably, an observation guide facilitates focused thinking and journaling about kids, giving parents and educators a tool for recognizing progress and knowing how to encourage children to live up to their potential.
Keywords: Child rearing,Parenting,Con nuôi,Nuôi dạy con; Religious aspects,Christianity,Religious aspects,Christianity,Khía cạnh tôn giáo,Kitô giáo,Khía cạnh tôn giáo,Kitô giáo